Efficiency and Energy Consumption of Partial Carbonation Process for CO2 Capture from Natural Gas Combustion - Rubens Coutinho Toledo; Caio Leandro de Moraes; Vinoth Thangarasu; João Andrade de Carvalho; Ivonete Avila (Energies)
Brazil has set a goal to reduce greenhouse gas (GHG) emissions, which is a significant opportunity to leverage calcium looping (CaL) technology for energy generation in natural gas power plants. CaL is a promising technology, due to sorbent low cost and availability, but its industrial implementation performance decay is a major challenge to face. While evaluating carbon-capture technologies, net emissions perspective is essential, and optimizing CaL capture through a partial carbonation cycle is a promising approach, both to reduce net emissions and improve the number of cycles before deactivation. In this context, a Brazilian dolomite was characterized and evaluated, to be used as sorbent in a CaL process employed in natural gas power plants. For such a purpose, a novel methodology has been proposed to evaluate the mass ratio of CO2 captured, to assess the energy consumed in the process. A rotatable central composite design (RCCD) model was used to identify the optimal temperature and residence time conditions in the carbonation stage of the CaL process, focusing on achieving energy efficiency. The five most promising conditions were then tested across 10 calcination–carbonation cycles, to examine the impact of partial carbonation in capture efficiency over extended cycles. The results indicate that temperature plays a critical role in the process, particularly in terms of capture efficiency, while residence time significantly affects energy consumption. The conditions that demonstrated optimal performance for both the single and the multi-cycle tests were 580 °C for 7.5 min and 550 °C for 10 min, given that index of capture efficiency (<semantics>IEC10,c</semantics>) values of 1.34 and 1.20 were found, respectively—up to 40% higher than at 475 °C. There was lower energy expenditure at 580 °C (<semantics>Esp</semantics>) (33.48 kJ), 550 °C (<semantics>Esp</semantics> = 37.97 kJ), <semantics>CO2</semantics> mass captured (<semantics>CO2cap</semantics> = 9.80 mg), and the samples exhibited a more preserved surface, thus making it the most suitable option for scale-up applications.